"We Are Here for You All the Way"—Patients' and Relatives' Experiences of Receiving Advanced Home Care. (September 2020) - Wennman, Ingela; Ringheim, Anna; Wijk, Helle
Background: It is of great importance to understand how patients and their close relatives experience the pros and cons of advanced home care so as to further develop this quickly growing choice of care. Objective: The aim of this study was to explore the experiences of receiving advanced home care among patients affected by life-threatening illness and their close relatives. Design: The study was an interview study conducted with patients in their homes. Some patient interviews were conducted together with a close relative participating. Setting/Participants: Patients registered in advanced home care in 2017 were offered the opportunity to participate in the study. The selection criteria were that the patient was within grade 3 of the Eastern Cooperative Oncology Group's Performance Status, older than 18 years, able to orient to time and place, and not newly registered. Analysis: The interviews were recorded and transcribed verbatim and analyzed with qualitative content analysis. Results: A total of 11 interviews were conducted: 8 with patients and 1 or 2 close relatives together; and 3 with the patient alone. It resulted in 3 main categories: create a safe environment, see the person, and better to manage care at home. Conclusion: The results of this study show that patients and close relatives perceived that advanced home care was a safe and secure form of caring during advanced as well as end-of-life care.